2018
DOI: 10.3389/fmicb.2018.00291
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Physiological Response of Oenococcus oeni to Ethanol Stress Using an Extended Genome-Scale Metabolic Model

Abstract: The effect of ethanol on the metabolism of Oenococcus oeni, the bacterium responsible for the malolactic fermentation (MLF) of wine, is still scarcely understood. Here, we characterized the global metabolic response in O. oeni PSU-1 to increasing ethanol contents, ranging from 0 to 12% (v/v). We first optimized a wine-like, defined culture medium, MaxOeno, to allow sufficient bacterial growth to be able to quantitate different metabolites in batch cultures of O. oeni. Then, taking advantage of the recently rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 92 publications
1
22
0
1
Order By: Relevance
“…However, the harsh environmental conditions of wine such as high ethanol concentration, low pH, and SO 2 , can often delay the growth of O. oeni and MLF process (G-Alegría et al, 2004 ; Olguín et al, 2015 ; Betteridge et al, 2017 ). Ethanol stress is generally considered as one of the main inhibitors of O. oeni growth in wine (Mendoza et al, 2017 ; Contreras et al, 2018 ). The strain O. oeni SD-2a is able to survive and grow in high ethanol conditions and shows strong MLF ability (Liu, 2002 ), however its ethanol stress response mechanism was still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the harsh environmental conditions of wine such as high ethanol concentration, low pH, and SO 2 , can often delay the growth of O. oeni and MLF process (G-Alegría et al, 2004 ; Olguín et al, 2015 ; Betteridge et al, 2017 ). Ethanol stress is generally considered as one of the main inhibitors of O. oeni growth in wine (Mendoza et al, 2017 ; Contreras et al, 2018 ). The strain O. oeni SD-2a is able to survive and grow in high ethanol conditions and shows strong MLF ability (Liu, 2002 ), however its ethanol stress response mechanism was still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the requirements of NAD(P) + and ATP increased during ethanol stress. The strain required 10 and 17 times more non-growth associated maintenance ATP during growth in medium containing 9% and 12% ethanol, respectively [29]. Therefore, the altered distribution of end-product yields in strain YUAN-3 indicates the need to redirect energy flow to maintain an efficient balance between ethanol stress response and growth.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, the effect of ethanol on the global metabolic response in Oenococcus oeni was carried out using an extended genome-scale metabolic model. The results indicated that the requirements of NAD(P) + and ATP increased in ethanol stress, and the strain required 10 and 17 times more ATP for non-growth associated maintenance during growth in medium containing 9% and 12% ethanol, respectively [29]. Therefore, these studies demonstrated that it is difficult to determine the microbial ethanol stress response mechanisms through limited proteins or pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The (F 0 F 1 ) H + -ATPases and MLF are closely linked and are essential in countering acid stress (Tourdot-Maréchal et al 1999). It has not been investigated which function of the (F 0 F 1 ) H + -ATPases dominate, but the use of a genome-scale metabolic model has facilitated the calculation of significant ATP production by ATPases as well as ATP consumption in non-growth associated maintenance, attributed to ATPases (Contreras et al 2018). In several studies it has been observed that MLF appears to start once the O. oeni population reaches approximately 1 × 10 6 colony-forming unit (CFU)/mL (Rice 1965, Rice and Mattick 1970, Silver and Leighton 1981, Liu and Gallander 1982, Versai et al 1999.…”
Section: Malolactic Fermentation Is An Essential Tool In Surviving Wimentioning
confidence: 99%